Zwietering's Equation for the Suspension of Porous Particles and the Use of Curved Blade Impellers - S. Ibrahim; S. N. Jasnin; S. D. Wong; I. F. Baker (International Journal of Chemical Engineering)
The minimum speed for just-suspension, Njs, of porous palm shell-activated carbon (PSAC) particles has been determined in a 15 cm diameter cylindrical tank using a 6-curved blade (6CB) impeller, compared to a 6-blade downpumping mixed-flow (6MFD) impeller and a Rushton turbine (6DT). The particles size ranged from 0.75–1.00 mm, 1.00–1.40 mm, and 1.40–2.36 mm with concentrations between 0 and 5% by weight. The 6CB being a radial impeller performed similarly to 6DT in terms of speed and power requirement at just-suspension, and particles distribution on the base. The 6MFD, with power requirement 100% to 200% less than the radial impellers, was the most efficient for suspending the particles, as usually reported for the range of solid concentrations used here. Specific power per unit mass for all three impellers showed reduction towards minima as the concentration of particles increased. The geometric factor, S, values agreed reasonably with published data, when the particle density was adjusted taking into account water filling the pores of the submerged activated carbon. This result means that Zwietering’s equation can be used to predict suspension for porous particles with adjustment to the particle density. S values for curved-blade impellers are presented for the first time.